2020
DOI: 10.1002/ijgo.13153
|View full text |Cite
|
Sign up to set email alerts
|

Amnioreduction in emergency cervical cerclage: A series of eight cases

Abstract: The authors have no conflicts of interest. predictions: An updated model building strategy illustrated with challenging industry case studies. Clin Pharmacokinet. 2019;58:727-746. 2. Ke AB, Greupink R, Abduljalil K. Drug dosing in pregnant women: Challenges and opportunities in using physiologically based pharmacokinetic modeling and simulations. CPT Pharmacometrics Syst Pharmacol. 2018;7:103-110. 3. Doravirine/Lamivudine/Tenofovir disoproxil fumarate fixed drug combination. FDA Center for Drug Evaluation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…A 2019 case series by Zhang et al . documented eight patients who underwent amnioreduction as an adjunct to cervical cerclage for cervical incompetence with benefits in prolonging GA.[ 5 ] With fetal OA, polyhydramnios will likely to recur hence close monitoring with repeated amnioreductions may prove beneficial. In our experience, both interventions were integral in prolonging gestation, thereby optimizing conditions for successful reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 case series by Zhang et al . documented eight patients who underwent amnioreduction as an adjunct to cervical cerclage for cervical incompetence with benefits in prolonging GA.[ 5 ] With fetal OA, polyhydramnios will likely to recur hence close monitoring with repeated amnioreductions may prove beneficial. In our experience, both interventions were integral in prolonging gestation, thereby optimizing conditions for successful reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of amnioreduction prior to ECC is to reduce intrauterine pressure. After amnioreduction, it can be observed that the distension of the membranes was markedly reduced and makes it easier to expose dilated cervical edge, in turn reducing the surgical difficulty and improving outcomes [21,[23][24][25][26]. In our study, 11 cases with advanced cervical dilation at least 3 cm, including two cases near fully dilated before the operation, underwent successful ECC without procedure-related rupture of membrane, suggesting that the amnioreduction may be a feasible option before ECC in such conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In 1979, Robert C. Goodwin reported for the first time the application of amnioreduction before ECC to reduce the tension of the protruding amniotic sac in the vagina [21]. Since then, several studies have reported on amnioreduction prior to ECC for bulging membranes, however, the pregnancy outcomes were inconsistent due to the heterogeneity of cases [22][23][24][25][26]. To improve the success of ECC procedure and pregnancy outcomes among patients with large bulging membranes, our hospital started to adopt amnioreduction prior to ECC since December 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Among those methods, amnioreduction facilitates the replacement of the protruding membrane by reducing the hydrostatic force. Through several studies, amnioreduction has been proven to be a feasible method [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%